Recombinants between avian sarcoma virus genome and chicken helper factor gene of the host cell: cloning by transfection. - Carloni, G (1980)
Chicken cells of chicken helper factor-positive (chf+) phenotype were infected with a cloned (envE-free) Rous sarcoma virus, subgroup D, and examined for the presence of parent and recombinant proviruses by transfection in chicken and turkey cells, respectively. It was found that most parent virus DNA is integrated into the host cell genome during the first 18 hr after infection, and no significant integration occurs between 18 and 72 hr after infection. On the other hand, no recombinant virus DNA was detected at 18 hr, although both unintegrated and integrated (provirus) forms of this DNA occurred 72 hr after infection. Recombination proviruses were also found in chronically virus-infected chf+ cells but not in chf- cells lacking virus-related RNA. Our results show that recombinants between the exogenous virus and endogenous chf gene can be cloned from the DNA of the host cell by transfection and suggest that a second replicative cycle of the virus is required to generate such recombinants.